2007
DOI: 10.1007/s11032-007-9151-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of a core set of informative genic SSR and SNP markers for assaying functional diversity in barley

Abstract: A 'core set' of 28 simple sequence repeat (SSR) and 28 single nucleotide polymorphism (SNP) markers for barley was developed after screening six diverse genotypes (DGs) representing six countries (Afghanistan, Pakistan, Algeria, Egypt, Jordan and Syria) with 50 SSR and 50 SNP markers derived from expressed sequence tags (ESTs). The markers of the core set are single locus with very high quality amplifications, high polymorphism information content (PIC) and are distributed across the barley genome. PIC values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 44 publications
2
44
1
1
Order By: Relevance
“…Among them, SSR marker BMAC0113 linked to QTLs for days to heading in barley (Pillen et al, 2003(Pillen et al, , 2004 was validated again through GLM analysis as it showed association with TEE. Moreover, EST-SSR marker GBM1464 that showed association with plant height in the present study was previously reported that had a functional association (Varshney et al, 2008). "Character-specific molecular markers" are positively considered by UPOV's BMT to be used in DUS testing, provided that they can reliably estimate traditional characteristics (UPOV, 2013).…”
Section: Discussionsupporting
confidence: 56%
“…Among them, SSR marker BMAC0113 linked to QTLs for days to heading in barley (Pillen et al, 2003(Pillen et al, , 2004 was validated again through GLM analysis as it showed association with TEE. Moreover, EST-SSR marker GBM1464 that showed association with plant height in the present study was previously reported that had a functional association (Varshney et al, 2008). "Character-specific molecular markers" are positively considered by UPOV's BMT to be used in DUS testing, provided that they can reliably estimate traditional characteristics (UPOV, 2013).…”
Section: Discussionsupporting
confidence: 56%
“…PIC was averaged over the fragments for each primer combination. The marker index was calculated as given in Varshney et al [25]:…”
Section: Discussionmentioning
confidence: 99%
“…PIC, which according to Varshney et al (2007) take into account the total number of fragments detected for each locus of a given primer and the frequency of these alleles in the set of genotypes investigated, in this study ranged from 0.70 (UBC 835) to 0.1468 (UBC 827), with mean of 0.4294.…”
Section: Molecular Characterizationmentioning
confidence: 94%